2022
DOI: 10.1002/cpt.2575
|View full text |Cite
|
Sign up to set email alerts
|

Estimands and Complex Innovative Designs

Abstract: Since the release of the ICH E9(R1) (International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use Addendum on Estimands and Sensitivity Analysis in Clinical Trials to the Guideline on Statistical Principles for Clinical Trials) document in 2019, the estimand framework has become a fundamental part of clinical trial protocols. In parallel, complex innovative designs have gained increased popularity in drug development, in particular in early development phases or in diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…For the assessment of estimators in clinical trials, the estimand framework [17] has become an important tool. While the estimand, defined as the target of estimation, is derived from the trial objective and is therefore not directly affected by the use of non-concurrent controls, the properties of estimators depend on if and how nonconcurrent controls are employed in the estimation of treatment effects [18]. Time trends can affect estimators through several aspects of the data generating process in a clinical trial, such as the study population, the measurement of endpoints, or the impact of intercurrent events.…”
Section: Discussionmentioning
confidence: 99%
“…For the assessment of estimators in clinical trials, the estimand framework [17] has become an important tool. While the estimand, defined as the target of estimation, is derived from the trial objective and is therefore not directly affected by the use of non-concurrent controls, the properties of estimators depend on if and how nonconcurrent controls are employed in the estimation of treatment effects [18]. Time trends can affect estimators through several aspects of the data generating process in a clinical trial, such as the study population, the measurement of endpoints, or the impact of intercurrent events.…”
Section: Discussionmentioning
confidence: 99%
“…Even then, the ethical challenges posed by umbrella trials need careful consideration ( 78 ). Furthermore, the use of the estimand framework in master protocols has become an area of growing consideration ( 79 , 80 ). This may lead to substantial transformations in the way umbrella trials should be analyzed and reported over the coming years which are not discussed in our work.…”
Section: Discussionmentioning
confidence: 99%
“…Early conclusions regarding antitumor activity are usually based on binary response endpoints, duration of response, and/or time to first response. In some studies, to use more information in decision making, it could be relevant to use methodology which facilitates borrowing information across different cohorts, 5 such as the exchangeability‐nonexchangeability approach (EXNEX) 6 and the multiple‐cohort expansion (MUCE, e.g., inferential basket studies) design 7 . We will restrict the scope of this paper to non‐comparative studies, binary response type endpoints, without information borrowing.…”
Section: Estimands To Assess Response In Oncology Clinical Trialsmentioning
confidence: 99%